Exploring GVS as a display modality: cutaneous sensations and cue association maintenance - Temple, David R.; Klausing, Lanna N.; Hogoboom, Brady C.; Datta, Abhishek; Clark, Torin K. (Experimental brain research, 2025)
Recent studies have investigated the potential use of Galvanic Vestibular Stimulation (GVS) as an alternative display modality. Such a GVS display could allow for parallel processing of information under increasing demands on other modalities (e.g., visual, auditory, or tactile), and perhaps be preferrable to other displays in certain circumstances (e.g., covert night operations). Prior studies quantified how precisely humans distinguish GVS cues modulated in the frequency, amplitude, or polarity of the sinusoidal burst of current, found cues to be robust to various environments, and have limited degradations in maintaining posture. Questions still arise though as to: (1) whether those receiving GVS cues respond primarily to vestibular or potentially cutaneous sensations, and (2) if multiple cues can be associated with different responses and if that capability can be maintained, which we addressed through two experiments. In the first, a topical anesthetic was not found to affect frequency and amplitude modulated GVS thresholds; however, polarity modulated GVS thresholds were elevated when cutaneous sensation was diminished. The second experiment revealed subjects distinguish among six different GVS cues composed of frequency (two conditions) and polarity (three conditions) modulations, and they maintained their association of these six cues three hours later. Collectively our results suggest that individuals are primarily responding to vestibular sensations when utilizing a GVS display and that quick association of at least six GVS cues to different responses can occur and be maintained at least three hours later. These findings continue to support the use of GVS as a viable display modality.